ANALISIS PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA LAYANAN JASA GOMED - Dini Dwi Ermawati; Angga Putri Ekanova (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the effect of promotion and service quality partially and simultaneously on consumer satisfaction with gomed services. The data analysis method in this study uses quantitative primary data obtained through distributing questionnaires to 100 respondents who are students who use gomed services and live in the Bekasi City area. The sampling method in this research is purposive sampling, namely the technique of determining the sample with certain considerations using the Non Probability sampling technique. The test stages carried out are Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Test, t Test (Partial), F Test (Simultaneous), and Coefficient of Determination Test (R2). The results of this study indicate that the promotion variable can partially and significantly affect consumer satisfaction on gofood services. The service quality variable can also partially and significantly affect consumer satisfaction with gomed services. There is a simultaneous and significant influence between promotion and service quality on consumer satisfaction with gomed services.